PHYSICAL AND TECHNICAL READINESS OF FIRST-YEAR FOOTBALL PLAYERS AT THE INITIAL TRAINING STAGE (Physical Culture and Sport: Scientific Perspective, 2025)
The number of children wishing to engage in football is increasing, as is the overall level of preparedness and the number of competitions. Significant attention is given to the training of football players within the system of youth sports schools and various sports clubs, with training often starting as early as three to five years old. To determine the level of physical and technical readiness of first-year football players at the initial training stage. Methods: Theoretical analysis and synthesis of scientific and methodological literature data, abstraction, historical method, comparison, pedagogical testing, and methods of mathematical statistics. The study involves 73 football players aged 6-7 years in Ivano-Frankivsk. The scientific analysis includes the formation of physical and technical training of young athletes. Specialists emphasize the importance of a comprehensive approach to training and the individual realization of football players' potential from the very beginning of their careers. The analysis shows that quality preparation requires considering many factors. The research covers the state of the neuromuscular system, the development of agility in children, training and coaching methods, technical-tactical activities, and more. With the development of football, there is a need to improve children's training programs by incorporating new knowledge and methodological approaches. The study also examines the readiness of athletes for educational and training activities. Control was conducted to determine trends in the readiness of young football players. The results show significant variability within groups, especially in tests on movement coordination and spinal mobility. Greater variability in results is observed in technical exercises such as goal kicks and ball juggling. The obtained results slightly lag behind previous studies, confirming the need to improve training programs.
Keywords: readiness; young football players; physical training; technical training; testing; pedagogical testing